2010
DOI: 10.1111/j.1600-9657.2010.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial and dental injuries of snowboarders in Turkey

Abstract: Seventeen snowboard riders had been affected by orofacial trauma. Results revealed that all snowboarders were aware of helmet protection whereas 50 out of 86 (58%) reported that they used them. It should be concluded that from the moment a youngster begins to practice snowboard riding, (s)he should be encouraged to wear a helmet and a properly fitted mouthguard as part of the necessary protection for them to safely enjoy their sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In contrast to these results, many authors indicated that falls was the main cause . Other studies reported that sport‐related activities and agriculture‐related activities were the main causes of maxillofacial–oral injuries. The rank of injury causes of our study was not similar to other studies.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to these results, many authors indicated that falls was the main cause . Other studies reported that sport‐related activities and agriculture‐related activities were the main causes of maxillofacial–oral injuries. The rank of injury causes of our study was not similar to other studies.…”
Section: Discussionmentioning
confidence: 76%
“…In these cases, both dentists and sports centre staff might suggest the use of helmets, mouthguards and/or facemasks suitable for the sport being practised, informing players of the risk of dental and facial damages and of the benefits of these safety measures [16, 3335].…”
Section: Introductionmentioning
confidence: 99%
“…e correct use of the helmet can protect against head injuries among riders snowboard when subjected to falls or collisions. However, there are a lot of practitioners who do not use the equipment, with 52.9% of the riders who have su ered dental or oral and facial trauma, reported not wearing a helmet 40 . e location of the nasal bone is anatomically potentially more vulnerable and to protect this region, it is important which the material used for manufacture the nose shield has the adequate capacity of shock absorption, such as ethylene vinyl acetate (EVA).…”
Section: Face Shieldsmentioning
confidence: 99%
“…However, the risk will be minimized because the damage depends on the magnitude and source of force, beyond the anatomical region reached 41 . Concomitant the use of face shields, an information program emphasizing importance of using protective clothing and education of urgency is essential and should be training routine 40 .…”
Section: Face Shieldsmentioning
confidence: 99%